Application of XP-Endo finisher files in the reduction of microbial load in oval-shaped root canals - An ex vivo study - Mantovani, Giovanna Dornelas; Gomes, Brenda Paula Figueiredo de Almeida; Louzada, Lidiane Mendes; Vasconcelos, Rodrigo Arruda; Carvalho, Maria Cristina; Zuolo, Mario Luis (Revista dos Trabalhos de Iniciação Científica da UNICAMP, 2019)
The present study evaluated the effectiveness of XP-Endo Finisher (XPF) associated with XP-Endo Shaper (XPS) or Reciproc Blue (RB) files in the reduction of Enterococcus faecalis in oval-shaped root canals. Eighty mandibular incisors with single oval-shaped root canals were contaminated with E. faecalis for 10 days at 37°C with centrifugation on alternate days. The teeth were randomly assigned to eight experimental groups (n=10) as follows: G1 – XP-Endo Shaper, G2 – XP-Endo Shaper + XP-Endo Finisher, G3 – Reciproc Blue, and G4 – Reciproc Blue + XP-Endo Finisher. Chemomechanical preparation was performed with saline solution (NaCl) or 2.5% sodium hypochlorite (NaOCl). Microbial reduction was assessed by colony forming units (CFU/mL) count before (S1) and after (S2) CMP by using sterile paper points. ANOVA, Tukey’s test and Bonferroni’s post-hoc tests were used at 5% significance level. Bacteria were present in all initial samples (P>.05). All instrumentation techniques reduced bacteria, irrespective of the irrigating solution (P